A method and application of preparing CsPbI3 perovskite film and high-efficiency solar cell under high humidity environment
By using methylamine acetate ionic liquid and regulating the ratio of lead iodide, efficient and stable CsPbI3 perovskite films and solar cells were prepared in high humidity environments, solving the challenges of perovskite solar cells in terms of humidity and air stability.
Patent Information
- Application Number
- CN202110117031.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-01-28
AI Technical Summary
All-inorganic perovskite solar cells have challenges in moisture and air stability, especially in high humidity environments where efficient and stable films and devices are difficult to prepare.
A methylamine acetate ionic liquid is used as the solvent for the CsPbI3 perovskite precursor solution. By regulating the ratio of lead iodide in the precursor solution, CsPbI3 perovskite films and solar cells are prepared in air with a relative humidity of 40%-80%.
It realizes the preparation of dense and uniform high-quality perovskite films and their solar cell devices under high humidity environments, and improves the moisture-heat stability and photoelectric conversion efficiency of the device.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a CsPbI3 perovskite film and a high-efficiency perovskite solar cell in air with a relative humidity of 40%-80% by adjusting the proportion of lead iodide in a precursor solution based on methylammonium acetate ionic liquid as a precursor solvent, in particular to a simple method for preparing a dense and uniform high-quality perovskite film and a solar cell device thereof in high-humidity air with a relative humidity of 40%-80%, and belongs to the field of optoelectronic materials and technology. Background Art
[0002] With the continuous development of society, environmental problems caused by traditional fossil energy have attracted more and more attention, and the development of clean energy is imminent. With the increasing demand for clean energy, solar power generation has attracted more and more attention. At present, the mainstream solar power generation devices on the market are mainly silicon-based solar cells, but expensive raw materials have become a bottleneck in their development, greatly limiting the industrial production of silicon-based solar cells.
[0003] Perovskite solar cells are simple to manufacture and low-cost, and their photoelectric conversion efficiency has increased rapidly from 3.8% to 25.5% since 2009. However, perovskite solar cells have poor thermal stability, which limits their commercial application. In order to improve the thermal stability of perovskite cells, researchers have proposed a method of replacing the organic part of the perovskite component with an inorganic part to prepare an all-inorganic perovskite, thereby improving the thermal, humidity and air stability of perovskite cells.
[0004] At present, the research on all-inorganic perovskite solar cells is mainly focused on optimizing the film and device structure, while there is relatively little research on the interaction between perovskite precursor components. In addition, the currently used solvents N,N-dimethylformamide (DMF) and N,N-dimethyl sulfoxide (DMSO) are toxic solvents, which greatly limits their commercial application. The present invention mainly uses the green solvent methylammonium acetate ionic liquid solvent as a precursor solvent to adjust the proportion of the precursor components, and uses a simple one-step method to prepare an all-inorganic perovskite CsPbI3 solar cell in air with a relative humidity of 40%-80% through the synergistic effect of methylammonium acetate and excess lead iodide, and finally obtains a high-efficiency solar cell device. Summary of the invention
[0005] The technical problem solved by the present invention is to solve the humidity and air stability of all-inorganic perovskite solar cells and their sensitivity to moisture in the air. A method for preparing an efficient and stable CsPbI3 perovskite film and a solar cell in the air is proposed based on methylammonium acetate ionic liquid as a solvent for a CsPbI3 perovskite precursor solution by regulating the proportion of lead iodide components.
[0006] To solve the above technical problems, the technical solution proposed by the present invention is: a method for preparing CsPbI3 perovskite thin films and high-efficiency perovskite solar cells in air with a relative humidity of 40%-80% by regulating the proportion of lead iodide in the precursor solution, comprising the following steps:
[0007] (1) Dissolve cesium iodide, dimethylamine hydroiodide and lead iodide in a molar ratio of 1:1:X (1 < X < 3) in methylammonium acetate solvent to prepare an all-inorganic perovskite precursor solution, and heat and stir to dissolve at a temperature above 100°C for 0.5 - 3 hours;
[0008] (2) Spin-coat the electron transport material on the transparent conductive FTO glass;
[0009] (3) Spin-coat the prepared perovskite precursor solution on the FTO conductive substrate with an electron transport layer, and obtain a flat and dense perovskite thin film through gradient annealing;
[0010] (4) Spin-coat a trimethylphenylammonium chloride solution interface modification layer on the perovskite layer
[0011] (5) Spin-coat a hole transport layer on the perovskite layer;
[0012] (6) Vacuum deposit an interface modification layer and a metal electrode on the hole transport layer.
[0013] Preferably, in the step (1), the concentration of the perovskite precursor solution is 100 - 400 mg / mL.
[0014] Preferably, in the step (2), the electron transport layer deposited on the transparent conductive FTO electrode is SnO2, and the specific steps are: after spin-coating SnO2, anneal at 150°C for 30 minutes.
[0015] Preferably, in the step (3), the heating spin-coating method is used, and the specific steps are as follows:
[0016] (1) The substrate temperature is 50 - 100°C;
[0017] (2) The spin-coating conditions are spin-coating at 1500 rpm for 10 seconds; spin-coating at 2500 rpm for 10 seconds; spin-coating at 4000 rpm for 10 seconds;
[0018] Preferably, in the step (3), the gradient annealing specific steps are 100 - 160°C for 2 - 10 minutes, 200 - 300°C for 2 - 10 minutes.
[0019] Preferably, in the step (4), the interface modification layer is trimethylphenylammonium chloride. The specific steps are as follows:
[0020] (1) Dissolve 1 mg of trimethylphenylammonium chloride in 1 mL of isopropanol solution;
[0021] (2) Stir the prepared trimethylphenyl ammonium chloride solvent at room temperature at a rotation speed of 300 rpm for 5 hours;
[0022] (3) Spin coat 40uL of trimethylphenylammonium chloride solution on the perovskite at 3000 rpm for 30 seconds.
[0023] Preferably, the hole transport layer in step (5) is Spiro-OMeTAD. The specific steps are as follows:
[0024] (1) Dissolve 85.8 mg of Spiro-OMeTAD in 1 mL of chlorobenzene;
[0025] (2) Dissolve 520 mg of bis(trifluoromethanesulfonic acid) imide lithium salt in 1 mL of acetonitrile solution;
[0026] (3) Add 39.0 μL of TBP solution to the Spiro-OMeTAD solution;
[0027] (4) Add 23.0 μL of lithium salt solution to the Spiro-OMeTAD solution;
[0028] (6) Add 12 μL of FK-209 to the Spiro-OMeTAD solution;
[0029] (7) stirring the mixed solution at room temperature for 2 hours;
[0030] (8) Spin coating condition: 3000 rpm for 30 seconds;
[0031] Preferably, in step (6), the interface modification layer is MoO3 and the metal electrode is Ag. The specific steps are:
[0032] (1) MoO3 is evaporated on the hole transport layer with a thickness of 5 nm;
[0033] (2) The thickness of the metal Ag electrode is 100 nm;
[0034] In order to solve the above technical problems, another technical solution proposed by the present invention is: a method for preparing a CsPbI3 perovskite film and a high-efficiency perovskite solar cell by adjusting the proportion of lead iodide in a precursor solution in air with a relative humidity of 40%-80%.
[0035] In order to solve the above technical problems, another technical solution proposed by the present invention is: a method of preparing CsPbI3 perovskite film and its high-efficiency perovskite solar cell in air with a relative humidity of 40%-80% by adjusting the proportion of lead iodide in the precursor solution, and applying the prepared perovskite solar cell in the optoelectronic field.
[0036] Beneficial effects of the present invention:
[0037] (1) The preparation of all-inorganic CsPbI3 perovskite films reported previously is all prepared in an inert gas environment or in air with a relative humidity of less than 30% by controlling the relative humidity of the air. However, the CsPbI3 perovskite film prepared by the present invention does not need to control the relative humidity of the air at a low level, which greatly reduces the harsh environmental requirements for its preparation. It can directly use methylammonium acetate ion solvent to control the proportion of lead iodide in the precursor under high humidity conditions (relative humidity of 40%-80%). The excess proportion of lead iodide can form a MAPbI3 intermediate phase with the methylamine cation in the methylammonium acetate ionic liquid, thereby promoting the phase transition process to prepare a CsPbI3 perovskite solar cell with excellent energy conversion efficiency, which is conducive to its industrialization.
[0038] (2) In a high humidity environment with an air humidity greater than 70%, the perovskite precursor solution is prepared by adjusting the proportion of PbI2 using methylammonium acetate ion solvent. Compared with the traditional DMF and DMSO solvents, it is precisely because of the synergistic effect of methylammonium acetate ions and excess lead iodide that the present invention greatly improves the wet thermal stability of the precursor solution, so that the film preparation can be successfully prepared under high humidity;
[0039] (3) By adding an excess amount of lead iodide in a high humidity environment with an air humidity greater than 70%, a dense, uniform, and large-grained CsPbI3 perovskite film was prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The present invention will be further described below in conjunction with the accompanying drawings.
[0041] Figure 1 is a thermogravimetric analysis diagram of the perovskite precursor solution in the present invention;
[0042] Figure 2 It is a UV-vis absorption spectrum of a CsPbI3 thin film prepared in the air by using methylamine acetate as a precursor solution solvent to control the proportion of PbI2 in the present invention;
[0043] Figure 3 This is a SEM image of the all-inorganic CsPbI3 perovskite film with large grain size prepared in the air by the present invention;
[0044] Figure 4 This is the XRD diagram of the all-inorganic CsPbI3 perovskite film prepared in the air by the present invention;
[0045] Figure 5 It is a structural diagram of the all-inorganic CsPbI3 perovskite solar cell device prepared in the air of the present invention;
[0046] Figure 6 The JV curves of the CsPbI3-free perovskite solar cell prepared in the air with relative air humidity of 30%, 60% and 80% respectively; DETAILED DESCRIPTION
[0047] Example 1
[0048] This embodiment is to use methylammonium acetate ionic liquid as the solvent of CsPbI3 perovskite precursor solution to prepare low defect state density, large grain size all-inorganic CsPbI3 perovskite film and its efficient and stable perovskite solar cell by adjusting the lead iodide ratio, so as to fully understand the laboratory humidity condition of the present invention is greater than 70%. It mainly includes the following steps:
[0049] Step 1) The etched FTO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 15 minutes each, dried with nitrogen, and then dried in an oven at 100° C. for 30 minutes to obtain a clean FTO substrate.
[0050] Step 2) 108.1 mg of cesium iodide, 162.2 mg of lead iodide and 71.9 mg of dimethylamine hydroiodide were weighed and dissolved in 1 mL of methylamine acetate solvent in a ratio of 1:1.5:1, and stirred at a temperature above 100°C for 2 hours until completely dissolved to prepare a perovskite precursor solution with a concentration of 300 mg / mL.
[0051] Step 3) 85.8 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene; 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solution; 39 μL of TBP solution was added to the Spiro-OMeTAD solution, and 23 μL of lithium salt solution was added to the Spiro-OMeTAD solution;
[0052] The mixed solution was stirred at room temperature for 2 hours; the spin coating condition was 3000 rpm for 30 seconds;
[0053] Step 4) Dissolve 1 mg of trimethylphenylammonium chloride in 1 mL of isopropanol solution and stir the solution at 300 rpm for 5 hours at room temperature; the spin coating condition is 3000 rpm for 30 seconds;
[0054] Step 5) The FTO substrate cleaned in step 1) is treated with ultraviolet ozone for 15 minutes.
[0055] Step 6) Take 45 μL of the electron transport material SnO2 and drop it onto the FTO substrate treated in step 4), and use a spin coater to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the FTO spin-coated with SnO2 at 150°C for 30 minutes.
[0056] Step 7) placing the FTO conductive substrate with the electron transport layer spun on after annealing in step 6) on a hot spin coater with a substrate temperature of 50-100° C. and preheating for 5 minutes.
[0057] Step 8) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the preheated FTO substrate in step 6), spin coat it into a film, and then anneal it to form a perovskite film. The rotation speed of the spin coating perovskite precursor solution is 1500 rpm for 10 seconds, 2500 rpm for 10 seconds, 4000 rpm for 10 seconds, and gradient annealing in air at 100-160°C for 2-10 minutes, and 200-300°C for 2-10 minutes.
[0058] Step 9) Spin-coating the interface modification material of trimethylphenylammonium chloride in step 4) onto the perovskite film in step 8), and the interface modification material of trimethylphenylammonium chloride is spin-coated at 3000 rpm for 30 seconds to form a trimethylphenylammonium chloride interface modification layer.
[0059] Step 10) Spin-coat the hole transport material of step 3) onto the perovskite film modified with trimethylphenylammonium chloride of step 9), and spin-coat Spiro-OMeTAD at 3000 rpm for 30 seconds to form a hole transport layer.
[0060] Step 11) uses vacuum evaporation technology to evaporate 5nm MoO3 on the hole transport layer of step 10), and then evaporate 100nm metal electrode Ag, so as to obtain a perovskite solar cell.
[0061] Step 12) Under standard test conditions (AM1.5 G illumination), the energy conversion efficiency of the battery device with the highest lead iodide ratio prepared in this example was 16.37%, the open circuit voltage was 1.10 V, and the short circuit current was 20.09 mA / cm 2 , the filling factor is 73.79%;
[0062] Example 2
[0063] This embodiment is to use methylammonium acetate ionic liquid as the solvent of CsPbI3 perovskite precursor solution to prepare low defect state density, large grain size all-inorganic CsPbI3 perovskite film and its efficient and stable perovskite solar cell by adjusting the lead iodide ratio, so as to fully understand the laboratory humidity condition of the present invention is greater than 70%. It mainly includes the following steps:
[0064] Step 1) The etched FTO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 15 minutes each, dried with nitrogen, and then dried in an oven at 100° C. for 30 minutes to obtain a clean FTO substrate.
[0065] Step 2) 108.1 mg of cesium iodide, 383.7 mg of lead iodide and 71.9 mg of dimethylamine hydroiodide were weighed and dissolved in 1 mL of methylamine acetate solvent in a ratio of 1:2:1, and stirred at a temperature above 100°C for 2 hours until completely dissolved to prepare a perovskite precursor solution with a concentration of 300 mg / mL.
[0066] Step 3) 85.8 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene; 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solution; 39 μL of TBP solution was added to the Spiro-OMeTAD solution, and 23 μL of lithium salt solution was added to the Spiro-OMeTAD solution;
[0067] The mixed solution was stirred at room temperature for 2 hours; the spin coating condition was 3000 rpm for 30 seconds;
[0068] Step 4) Dissolve 1 mg of trimethylphenylammonium chloride in 1 mL of isopropanol solution and stir the solution at 300 rpm for 5 hours at room temperature; the spin coating condition is 3000 rpm for 30 seconds;
[0069] Step 5) The FTO substrate cleaned in step 1) is treated with ultraviolet ozone for 15 minutes.
[0070] Step 6) Take 45 μL of the electron transport material SnO2 and drop it onto the FTO substrate treated in step 4), and use a spin coater to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the FTO spin-coated with SnO2 at 150°C for 30 minutes.
[0071] Step 7) placing the FTO conductive substrate with the electron transport layer spun on after annealing in step 6) on a hot spin coater with a substrate temperature of 50-100° C. and preheating for 5 minutes.
[0072] Step 8) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the preheated FTO substrate in step 6), spin coat it into a film, and then anneal it to form a perovskite film. The rotation speed of the spin coating perovskite precursor solution is 1500 rpm for 10 seconds, 2500 rpm for 10 seconds, 4000 rpm for 10 seconds, and gradient annealing in air at 100-160°C for 2-10 minutes, and 200-300°C for 2-10 minutes.
[0073] Step 9) Spin-coating the interface modification material of trimethylphenylammonium chloride in step 4) onto the perovskite film in step 8), and the interface modification material of trimethylphenylammonium chloride is spin-coated at 3000 rpm for 30 seconds to form a trimethylphenylammonium chloride interface modification layer.
[0074] Step 10) Spin-coat the hole transport material of step 3) onto the perovskite film modified with trimethylphenylammonium chloride of step 9), and spin-coat Spiro-OMeTAD at 3000 rpm for 30 seconds to form a hole transport layer.
[0075] Step 11) uses vacuum evaporation technology to evaporate 5nm MoO3 on the hole transport layer of step 10), and then evaporate 100nm metal electrode Ag, so as to obtain a perovskite solar cell.
[0076] Step 12) Under standard test conditions (AM1.5 G illumination), the performance parameters of the perovskite battery device prepared in this example are: energy conversion efficiency of 17.43%, open circuit voltage of 1.14V, short circuit current of 19.78mA / cm 2 , the filling factor is 77.35%;
[0077] Example 3
[0078] This embodiment is to use methylammonium acetate ionic liquid as the solvent of CsPbI3 perovskite precursor solution to prepare low defect state density, large grain size all-inorganic CsPbI3 perovskite film and its efficient and stable perovskite solar cell by adjusting the lead iodide ratio, so as to fully understand the laboratory humidity condition of the present invention is greater than 70%. It mainly includes the following steps:
[0079] Step 1) The etched FTO conductive glass was ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 15 minutes each, dried with nitrogen, and then dried in an oven at 100° C. for 30 minutes to obtain a clean FTO substrate.
[0080] Step 2) 108.1 mg of cesium iodide, 324.3 mg of lead iodide and 71.9 mg of dimethylamine hydroiodide were weighed and dissolved in 1 mL of methylamine acetate solvent in a ratio of 1:3:1, and stirred at a temperature above 100°C for 2 hours until completely dissolved to prepare a perovskite precursor solution with a concentration of 300 mg / mL.
[0081] Step 3) 85.8 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene; 520 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solution; 39 μL of TBP solution was added to the Spiro-OMeTAD solution, and 23 μL of lithium salt solution was added to the Spiro-OMeTAD solution;
[0082] The mixed solution was stirred at room temperature for 2 hours; the spin coating condition was 3000 rpm for 30 seconds;
[0083] Step 4) Dissolve 1 mg of trimethylphenylammonium chloride in 1 mL of isopropanol solution and stir the solution at 300 rpm for 5 hours at room temperature; the spin coating condition is 3000 rpm for 30 seconds;
[0084] Step 5) The FTO substrate cleaned in step 1) is treated with ultraviolet ozone for 15 minutes.
[0085] Step 6) Take 45 μL of the electron transport material SnO2 and drop it onto the FTO substrate treated in step 4), and use a spin coater to spin coat it into a film at a speed of 4000 rpm for 30 seconds, and then anneal the FTO spin-coated with SnO2 at 150°C for 30 minutes.
[0086] Step 7) placing the FTO conductive substrate with the electron transport layer spun on after annealing in step 6) on a hot spin coater with a substrate temperature of 50-100° C. and preheating for 5 minutes.
[0087] Step 8) Take 100 μL of the perovskite precursor solution prepared in step 2) and drop it onto the preheated FTO substrate in step 6), spin coat it into a film, and then anneal it to form a perovskite film. The rotation speed of the spin coating perovskite precursor solution is 1500 rpm for 10 seconds, 2500 rpm for 10 seconds, 4000 rpm for 10 seconds, and gradient annealing in air at 100-160°C for 2-10 minutes, and 200-300°C for 2-10 minutes.
[0088] Step 9) Spin-coating the interface modification material of trimethylphenylammonium chloride in step 4) onto the perovskite film in step 8), and the interface modification material of trimethylphenylammonium chloride is spin-coated at 3000 rpm for 30 seconds to form a trimethylphenylammonium chloride interface modification layer.
[0089] Step 10) Spin-coat the hole transport material of step 3) onto the perovskite film modified with trimethylphenylammonium chloride of step 9), and spin-coat Spiro-OMeTAD at 3000 rpm for 30 seconds to form a hole transport layer.
[0090] Step 11) uses vacuum evaporation technology to evaporate 5nm MoO3 on the hole transport layer of step 10), and then evaporate 100nm metal electrode Ag, so as to obtain a perovskite solar cell.
[0091] Step 12) Under standard test conditions (AM1.5 G illumination), the performance parameters of the perovskite battery device prepared in this example are: energy conversion efficiency of 17.16%, open circuit voltage of 1.13V, short circuit current of 19.99mA / cm 2 , the filling factor is 75.61%;
[0092] Comparative Example 1
[0093] The preparation of CsPbI3 perovskite film using traditional DMF / DMSO solvent according to the molar ratio of cesium iodide, lead iodide and dimethylamine hydroiodide of 1:2:1 requires operation in a vacuum glove box or under extremely low air humidity (relative air humidity is less than 30%), and the prepared perovskite film has a small grain size. However, by using methylammonium acetate ionic liquid as the solvent of CsPbI3 perovskite precursor solution, the proportion of lead iodide in the precursor solvent is adjusted so that the two can play a synergistic role in the preparation of high-efficiency CsPbI3 perovskite film and solar cell in air with a relative humidity of 40%-80%. The prepared perovskite film has a size of micrometer level and a dense and smooth morphology, and the prepared perovskite device has excellent device efficiency. (As shown in the attached figure) Figure 3 and 6 )
[0094] Comparative Example 2
[0095] In an air environment with a relative air humidity of more than 70%, methylammonium acetate ionic liquid is used as a precursor solution, and the energy conversion efficiencies of cesium iodide, lead iodide and dimethylamine hydroiodide in the ratios of 1:1:1, 1:2:1 and 1:3:1 are 12.39%, 17.43% and 17.16% respectively. In a glove box, a CsPbI3 perovskite solar cell is prepared using a traditional DMF / DMSO solvent under the condition of the above-mentioned optimal cesium iodide, lead iodide and dimethylamine hydroiodide ratio of 1:2:1, and its efficiency is 11.46%. Therefore, the present invention regulates the ratio of excess lead iodide, thereby playing a synergistic role with the methylammonium acetate ionic liquid, and the excess lead iodide can kinetically promote the formation of the CsPbI3 perovskite film to obtain an all-inorganic CsPbI3 solar cell with excellent efficiency.
[0096] In general, the present invention is based on methylammonium acetate ionic liquid as the solvent of CsPbI3 perovskite precursor solution, and the ratio of lead iodide in the precursor solvent is adjusted so that the two can play a synergistic role in preparing high-efficiency CsPbI3 perovskite film and solar cell in air with a relative humidity of 40%-80%. The prepared perovskite film has a size of micron level and a dense and smooth morphology, and the prepared perovskite device has excellent device efficiency. The all-inorganic CsPbI3 perovskite solar cell prepared by this method is simple to operate, has a high photoelectric conversion efficiency, and does not need to worry about the impact of the high humidity air environment on it, and has a rare industrialization advantage.
[0097] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. A method for preparing a CsPbI3 perovskite solar cell in a high humidity environment, characterized in that: It includes the following steps: (1) Dissolve cesium iodide, dimethylammonium hydroiodide, and lead iodide in a molar ratio of 1:1:X, where 1 < X < 3, in a methylammonium acetate solvent to prepare a perovskite precursor solution of all-inorganic CsPbI3, and heat and stir at a temperature above 100 °C for 0.5 - 3 hours; (2) Spin-coat and deposit an electron transport material on a cleaned and treated FTO transparent conductive glass sheet; (3) Spin-coat the prepared perovskite precursor solution on an FTO conductive substrate with an electron transport layer in air with a relative humidity of 40% - 80%, and perform gradient annealing at 100 - 160 °C for 2 - 10 minutes and 200 - 300 °C for 2 - 10 minutes to obtain a flat and dense perovskite thin film; (4) Spin-coat a trimethylphenylammonium chloride solution interface modification layer on the perovskite layer; (5) Spin-coat a hole transport layer on the perovskite layer; (6) Vacuum deposit an interface modification layer and a metal electrode on the hole transport layer.
2. The method for preparing a CsPbI3 perovskite solar cell under a high humidity environment according to claim 1, characterized in that: In the step (1), the concentration of the CsPbI3 perovskite precursor solution is 100 - 400 mg / mL.
3. The method for preparing a CsPbI3 perovskite solar cell under a high humidity environment according to claim 1, characterized in that: In the step (2), the electron transport layer on the transparent conductive FTO glass is SnO2, and the specific steps are as follows: (1) The spin-coating condition is to spin at 4000 revolutions for 30 seconds, (2) After spin-coating, anneal at 150 °C for 30 minutes.
4. The method for preparing a CsPbI3 perovskite solar cell under a high humidity environment according to claim 1, characterized in that: In the step (3), the thin film preparation is carried out by heating and stepwise spin-coating and gradient annealing in air with a relative humidity of 40% - 80%, and the specific steps are as follows: (1) The substrate temperature is 50 - 100 °C; (2) The spin-coating conditions are to spin at 1500 revolutions for 10 seconds; spin at 2500 revolutions for 10 seconds; spin at 4000 revolutions for 10 seconds; (3) After spin-coating, anneal at a gradient temperature, with the conditions of 100 - 160 °C for 2 - 10 minutes and 200 - 300 °C for 2 - 10 minutes.
5. The method for preparing a CsPbI3 perovskite solar cell under a high humidity environment according to claim 1, characterized in that: In the step (4), the spin-coated and deposited interface modification layer is a PTACl passivation layer; the specific steps are as follows: (1) Dissolve 1 mg of trimethylphenylammonium chloride in 1 mL of isopropanol solution; (2) Stir the prepared trimethylphenylammonium chloride solvent at room temperature at a rotation speed of 300 rpm for 5 hours; (3) Take 40 μL of the trimethylphenylammonium chloride solution and spin-coat it on the perovskite, with the spin-coating condition of 3000 revolutions for 30 s.
6. The method for preparing a CsPbI3 perovskite solar cell under a high humidity environment according to claim 1, characterized in that: In the step (5), the spin-coated and deposited hole transport layer is Spiro-OMeTAD; the specific steps are as follows: (1) Dissolve 85.8 mg of Spiro-OMeTAD in 1 mL of chlorobenzene; (2) Dissolve 520 mg of lithium bis(trifluoromethanesulfonyl)imide in 1 mL of acetonitrile solution; (3) Add 39.0 μL of TBP solution to the Spiro-OMeTAD solution; (4) Add 23.0 μL of the lithium salt solution to the Spiro-OMeTAD solution; (5) Add 12 μL of FK-209 to the Spiro-OMeTAD solution; (6) Stir the mixed solution at room temperature for 2 hours; (7) The spin-coating condition is 3000 revolutions for 30 s.
7. The method for preparing a CsPbI3 perovskite solar cell under a high humidity environment according to claim 1, characterized in that: In the step (6), the interface modification layer is MoO3, the metal electrode is Ag, and the specific steps are: (1) MoO3 is evaporated on the hole transport layer with a thickness of 5 nm; (2) The thickness of the metal Ag electrode is 100 nm.
8. A CsPbI3 perovskite solar cell prepared according to any one of claims 1-7.
9. Application of the CsPbI3 perovskite solar cell according to claim 8 in the field of optoelectronics.
Citation Information
Patent Citations
Stable and high-efficiency two-dimensional layered perovskite solar cell and preparation method therefor
CN108365102A
Perovskite solar cell prepared based on acetic acid-methylamine room-temperature molten salt as green solvent and method and application of perovskite solar cell
CN108666424A